Incidence, characteristics, determinants and prognostic impact of recurrent syncope. (25th November 2020) - Zimmermann, T; Du Fay De Lavallaz, J; Nestelberger, T; Gualandro, D; Badertscher, P; Lopez-Ayala, P; Widmer, V; Freese, M; Twerenbold, R; Wussler, D; Koechlin, L; Walter, J; et al.
Abstract: Background: The incidence, characteristics, determinants, and prognostic impact of recurrent syncope are largely unknown, causing uncertainty for both patients and physicians. Methods: We characterized recurrent syncope including sex-specific aspects and its impact on death and major adverse cardiovascular events (MACE) in a large prospective international multicenter study enrolling patients ≥40 years presenting with syncope to the emergency department (ED). Syncope etiology was centrally adjudicated by two independent and blinded cardiologists using all information becoming available during syncope work-up and 12-month follow-up. MACE were defined as a composite of all-cause death, acute myocardial infarction, surgical or percutaneous coronary intervention, life-threatening arrhythmia including cardiac arrest, pacemaker or implantable cardioverter defibrillator implantation, valve intervention, heart-failure, gastrointestinal bleeding or other bleeding requiring transfusion, intracranial hemorrhage, ischemic stroke or transient ischemic attack, sepsis and pulmonary embolism. Results: Incidence of recurrent syncope among 1790 patients was 20% (95%-confidence interval (CI) 18% to 22%) within 24 months. Patients with an adjudicated final diagnosis of cardiac syncope (hazard ratio (HR) 1.50, 95%-CI 1.11 to 2.01) or syncope of unknown etiology even after central adjudication (HR 2.11, 95%-CI 1.54 to 2.89) had an increased risk for syncope recurrence (Figure). LASSO regression fit on all patient information available early in the ED identified more than three previous episodes of syncope as the only independent predictor for recurrent syncope (HR 2.13, 95%-CI 1.64 to 2.75). Recurrent syncope within the first 12 months after the index event carried an increased risk for all-cause death (HR 1.59, 95%-CI 1.06 to 2.38) and MACE (HR 2.24, 95%-CI 1.67 to 3.01), whereas recurrences after 12 months did not have a significant impact on outcome measures. Conclusion: Recurrence rates of syncope are substantial and vary depending on syncope etiology. There seem to be no reliable patient characteristics available early on the ED that allow for the prediction of recurrent syncope with only a history of more than three previous syncope being associated with a higher risk for future recurrences. Importantly, recurrent syncope within the first 12 months carries an increased risk for death and MACE. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Swiss National Science Foundation, Swiss Heart Foundation